Pemahaman Konsep Matematika dengan Teknik Scaffoldıng: Systematic Literature Review - Bawadi, Sanggiti; Pujiastuti, Heni; Fathurrohman, Maman (Universitas Mathla'ul Anwar Banten, 2023)
Understanding mathematical concepts is one of the basics in learning mathematics, so scaffolding is part of the basic technique for building and developing strategies in learning. This study aims to conduct a literature review related to the effectiveness of the scaffolding technique in understanding mathematical concepts in mathematics learning. The research method chosen in this study is the Systematic Literature Review (SLR) method. Data collection was carried out by documenting and reviewing all articles related to mathematics education published between 2012 and 2022. The articles used in the studywere found to be 809 articles and after being selected there were 14 articles that met the inclusion criteria for analysis in accredited national and international journals obtained from Sinta Indonesia, Google Scholar, Digital Reference Center (Garuda) and Education Resources Information Center (ERIC), CiteSeerx, Indonesia one Search (IOS). Based on this study, it was found that the scaffolding technique was able to improve understanding of concepts in mathematics learning and could be developed from kindergarten to college for students.